The books of Haggai and Malachi - Verhoef, Pieter A. (Grand Rapids, MI Eerdmans, 1987)
Includes bibliographcial references and index.
Keywords: Bible. O.T. Haggai -- commentaries; Bible. O.T. Malachi -- commentaries